5
$\begingroup$

Evaluate in closed form: $$ \sum_{m=0}^\infty \sum_{n=0}^\infty \sum_{p=0}^\infty\frac{m!n!p!}{(m+n+p+2)!}$$

I tried to use same method for similar question and two variables.Was not able to get the final answer. Question proposed by Jalil Hajimir -- Infinite Series $\sum_{m=0}^\infty\sum_{n=0}^\infty\frac{m!\:n!}{(m+n+2)!}$

$\endgroup$
0
3
$\begingroup$

In the book (Almost) Impossible Integrals, Sums, and Series, page $533$, the result in $(6.291)$, it is easily shown by transforming the Gamma summand into a summand involving a product of Beta function (which we can further deal with using the integral representation of Beta function) that $$\sum_{i=1}^{\infty}\left( \sum_{j=1}^{ \infty} \frac{\Gamma(i)\Gamma(j)\Gamma(x)}{\Gamma(i+j+x)}\right)=\frac{1}{2}\left(\psi^{(1)}\left(\frac{x}{2}\right)-\psi^{(1)}\left(\frac{1+x}{2}\right)\right).$$

Now, replacing $x$ by $k$, considering the summation from $k=1$ to $\infty$, passing from Gamma function to factorials and reindexing the series, we get in the left-hand side the series the Op is interested in, and in the right-hand side a simple telescoping sum involving Trigamma function. The answer is indeed $\pi^2/4$.

$\endgroup$
4
$\begingroup$

Playing with Mathematica a bit and you will see that the sum is $$ S(3)=\sum_{p=0}^\infty \sum_{m=0}^\infty \sum_{n=0}^\infty\frac{m!n!p!}{(m+n+p+3)!} = \frac{1}{12} \left(3 \zeta (3)+2 \pi ^2 \log (2)\right)+ \sum _{n=1}^{\infty } \left(\frac{\psi ^{(1)}(n)}{4 n (2 n-1)}-\frac{\psi ^{(1)}\left(n+\frac{1}{2}\right)}{4 n (2 n-1)}\right) $$ where $\psi$ is the digamma function. It does not look like it can be further simplified.


Curiously though, a slightly different sum do has a closed form $$ S(2)=\sum_{p=0}^\infty \sum_{m=0}^\infty \sum_{n=0}^\infty\frac{m!n!p!}{(m+n+p+2)!} =\pi^2/4 $$ To see this, one can check $$ S(2) =\sum_{p=0}^\infty \sum_{m=0}^\infty\frac{m! p!}{(m+p+1)^2 (m+p)!} =\sum_{p=0}^\infty\frac{\, _3F_2(1,1,p+1;p+2,p+2;1)}{(p+1)^2} =:\sum_{p=0}^\infty a_p $$

Mathematica cannot simplify this anymore, but look at the first few terms $$ \frac{\pi ^2}{6},\frac{1}{6} \left(12-\pi ^2\right),\frac{1}{6} \left(\pi ^2-9\right),\frac{1}{18} \left(31-3 \pi ^2\right),\frac{1}{72} \left(12 \pi ^2-115\right),\frac{3019-300 \pi ^2}{1800},\frac{1}{600} \left(100 \pi ^2-973\right),\frac{48877-4900 \pi ^2}{29400} $$ The pattern is quite obvious, we should have $$ a_{2p}+a_{2p+1}= \frac{2}{(2 p+1)^2}, \quad p \ge 0. $$ So $$ S(2)=\sum_{p \ge 0} \frac{2}{(2 p+1)^2} = \pi^2/4. $$

$\endgroup$
4
  • $\begingroup$ Original question is not 3 it is 2 $\endgroup$ – Keon Dec 10 '19 at 23:03
  • $\begingroup$ fWhen it is 2 it has a closed form. $\endgroup$ – Keon Dec 10 '19 at 23:07
  • $\begingroup$ @Keon The question and the title does not match. $\endgroup$ – ablmf Dec 10 '19 at 23:10
  • $\begingroup$ It is fixed. Now both of them are 2 $\endgroup$ – Keon Dec 10 '19 at 23:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.